Effective Migraine Treatment in Pregnant and Lactating Women: A Practical Guide - Marcus, Dawn; Bain, Philip A. (Humana Press : Imprint: Humana, 2009)
More than 28 million Americans suffer from migraine headaches, with migraine affecting nearly one in five women in their reproductive years. Effective Migraine Treatment in Pregnant and Lactating Women: A Practical Guide, provides a comprehensive resource to address diagnosis, testing, and treatment of headaches in reproductively fertile women. This important new book offers a wealth of practical, ready-to-use, clinically tested tips and recommendations to treat women with headaches during pregnancy and nursing. Although women may ideally prefer to restrict migraine treatments during pregnancy, up to one in three pregnant women self-medicate for symptoms, especially with analgesics. Fortunately, there are many effective treatment options that can be safely used when pregnant and breastfeeding. Available therapies include medication and nonmedication treatments, traditional and alternative therapies, and nutritional supplements. This book uniquely answers frequently asked questions by patients and offers healthcare providers easy-to-use office tools for patient education and charting documentation. The authors of this important new work have collaborated to provide a resource that will help clinicians provide women with the tools and knowledge to become empowered and to gain control over their migraines when trying to conceive, during pregnancy, and when nursing.